A cytosine modification mechanism revealed by the structure of a ternary complex of deoxycytidylate hydroxymethylase from bacteriophage T4 with its cofactor and substrate. (2019) - Park, Si Hoon; Suh, Se Won; Song, Hyun Kyu
No abstract available